A Systematic Review of Melatonin in Plants: An Example of Evolution of Literature - Murch, Susan J.; Erland, Lauren A. E. (Frontiers in Plant Science, 2021)
Melatonin (N-acetyl-5-methoxy-tryptamine) is a mammalian neurohormone, antioxidant and signaling molecule that was first discovered in plants in 1995. The first studies investigated plant melatonin from a human perspective quantifying melatonin in foods and medicinal plants and questioning whether its presence could explain the activity of some plants as medicines. Starting with these first handful of studies in the late 1990s, plant melatonin research has blossomed into a vibrant and active area of investigation and melatonin has been found to play critical roles in mediating plant responses and development at every stage of the plant life cycle from pollen and embryo development through seed germination, vegetative growth and stress response. Here we have utilised a systematic approach in accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocols to reduce bias in our assessment of the literature and provide an overview of the current state of melatonin research in plants, covering 1995-2021. This review provides an overview of the biosynthesis and metabolism of melatonin as well as identifying key themes including: abiotic stress responses, root development, light responses, interkingdom communication, phytohormone and plant signaling. Additionally, potential biases in the literature are investigated and a birefringence in the literature between researchers from plant and medical based which has helped to shape the current state of melatonin research. Several exciting new opportunities for future areas of melatonin research are also identified including investigation of non-crop and non-medicinal species as well as characterization of melatonin signaling networks in plants.